The Long-Term Effects of Prematurity and Intrauterine Growth Restriction on Cardiovascular, Renal, and Metabolic Function - Patricia Y. L. Chan; Jonathan M. Morris; Garth I. Leslie; Patrick J. Kelly; Eileen D. M. Gallery (Hindawi Limited, 2010)
Objective. To determine relative influences of intrauterine growth restriction (IUGR) and preterm birth on risks of cardiovascular, renal, or metabolic dysfunction in adolescent children. Study Design. Retrospective cohort study. 71 periadolescent children were classified into four groups: premature small for gestational age (SGA), premature appropriate for gestational age (AGA), term SGA, and term AGA. Outcome Measures. Systolic blood pressure (SBP), augmentation index (Al), glomerular filtration rate (GFR) following protein load; plasma glucose and serum insulin levels. Results. SGA had higher SBP (average 4.6 mmHg) and lower GFR following protein load (average 28.5 mL/min/1.73 m2) than AGA. There was no effect of prematurity on SBP (P=.4) or GFR (P=.9). Both prematurity and SGA were associated with higher AI (average 9.7%) and higher serum insulin levels 2 hr after glucose load (average 15.5 mIU/L) than all other groups. Conclusion. IUGR is a more significant risk factor than preterm birth for later systolic hypertension and renal dysfunction. Among children born preterm, those who are also SGA are at increased risk of arterial stiffness and metabolic dysfunction.